2008
DOI: 10.4137/cmu.s718
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Randomized Clinical Trial of the Action of Several Doses of Lycopene in Localized Prostate Cancer: Administration Prior to Radical Prostatectomy

Abstract: Purpose: The purpose of this Phase II randomized-controlled trial was to evaluate the safety and effect of administering several doses of lycopene to men with clinically localized prostate cancer, on intermediate endpoint biomarkers implicated in prostate carcinogenesis.Methods: Forty-fi ve eligible men with clinically localized prostate cancer were supplemented with 15, 30 or 45 mg of lycopene or no supplement from biopsy to prostatectomy. Compliance to study agent, toxicity, changes in plasma lycopene, serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 47 publications
1
78
2
1
Order By: Relevance
“…This increased availability has encouraged subjects to opt out of participation in randomized clinical trials, where they have a chance at being assigned to a placebo arm [9,22,23]. Subjects have been unwilling to be randomized to placebo-control arms of trials, especially if the trial involves immense burden to them such as compliance to agent and diet, frequent visits, completion of monitoring tools and most importantly if these studies include invasive procedures for biomarker evaluation such as biopsy, fine needle aspirations or bronchoscopy [21].…”
Section: Discussionmentioning
confidence: 99%
“…This increased availability has encouraged subjects to opt out of participation in randomized clinical trials, where they have a chance at being assigned to a placebo arm [9,22,23]. Subjects have been unwilling to be randomized to placebo-control arms of trials, especially if the trial involves immense burden to them such as compliance to agent and diet, frequent visits, completion of monitoring tools and most importantly if these studies include invasive procedures for biomarker evaluation such as biopsy, fine needle aspirations or bronchoscopy [21].…”
Section: Discussionmentioning
confidence: 99%
“…The patients were supplemented with lycopene during the time of biopsy to prostatectomy. It was found that the plasma lycopene increased while the level of serum free testosterone decreased after lycopene administration [78], suggesting that lycopene could suppress PSA expression. Indeed, lycopene supplements did reduce the expression of PSA in localized PCa [79].…”
Section: The Role Of Nutraceuticals In the Inhibition Of Pcamentioning
confidence: 99%
“…Select soy isoflavones (namely, geinstein and daidzein) have weak estrogenic properties [81] and thus have been reported to exert antiproliferative effects on PCa due to suppression of AR-signaling pathways [8285]. Indeed, consumption of soy food appears to be associated with a 30% reduction in PCa risk in the epidemiological studies, which were primarily conducted in populations with diets traditionally high in soy [86].…”
Section: Pca Chemoprevention In Aammentioning
confidence: 99%
“…Soy isoflavones are known to influence multiple cellular pathways leading to aforementioned anticancerous effects; the authors recommend the following comprehensive review for detailed description of action of soy isoflavones on PCa [89]. Because down regulating the AR-mediated proliferation is thought to be one of the main mechanisms by which soy isoflavones exert its PCa chemopreventive action [8285], it appears biologically plausible that AAM would have a different (and better) response to the intervention using this compound. Although no published data are available on soy isoflavones effectiveness specifically in AAM, there is a currently active phase II clinical trial of Purified Isoflavones in PCa (NCT01036321, Kumar P.I.…”
Section: Pca Chemoprevention In Aammentioning
confidence: 99%
See 1 more Smart Citation